MITOS KEHAMILAN DALAM BUDAYA MASYARAKAT NAGARI GUAK PANJANG KOTO BARU KABUPATEN SOLOK - Fauziatussa'adiyah fauziatussa'adiyah (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Minangkabau women is a part of culture who has significant role in rumah gadang. In Minangkabau, a woman also called bundo kanduang. The next generation of culture was born through her.The honor to Minangkabau woman is related to her standing and her function ini daily life. She attempt to be cared with the environment. It starts with educate the children with religious and cultural teachings. So that, they could be the next generation who know the rights and obligations as Minangkabau society. Educating children is not only when they are physically born in this world, but it can be started when they are in the mother’s womb. Therefore, the ancestors have myths that related with pregnancy. It contains the element of goodness that radiated from the myth’s cultural value. In relation to gender, pregnancy’s myth in Minangkabau also addressed to men. This is related to results and findings from the pregnancy’s myth. Cultural value in pregnancy’s myth have a power to organize the behavior of human. In the other words, the values in it can apply to all layers of society. So that, this research is qualitative research. The aim of this research is to describe the gender equality in pregnancy’s myth of Minangkabau through cultural value